PENCEGAHAN DAN PENANGANAN KEKERASAN PADA ANAK DI KABUPATEN SAMPANG MELALUI PROGRAM CEKATAN - Christiana, Elisa; Haris H, Ernia; Ferdina, Cucun Setya; Nugrahani, Cantika Iva; Jufrianto, M.; Furqon, Muhammad (Jurnal Abdimas Bina Bangsa, 2024)
The CEKATAN Program (Preventing Sexual Violence Against Children) represents a comprehensive initiative between Madura State Polytechnic and, the Department of Social Services, Women's Empowerment, and Child Protection of Sampang Regency. This program emphasizes community involvement to optimize efforts in preventing sexual violence against children. The objectives of this initiative include identifying trends in child abuse, gathering cross-sectoral information related to child violence, providing support to child protection workers (PPA) in each district, and reporting cases to promote a "Zero Tolerance for Sexual Violence" policy. The CEKATAN program is implemented through Focus Group Discussions (FGDs), designed to analyze issues of violence against children. Key activities include signing a collective commitment, identifying issues of child violence, and delivering expert presentations. The FGD outcomes are a report on child violence issues and a collective agreement to prevent and address child abuse. This community service activity will proceed with a follow-up program, focusing on developing a policy brief on child violence prevention and handling strategies for Sampang Regency.